Identification of a Novel Pathogen Using Family-Wide PCR: Initial Confirmation of COVID-19 in Thailand - Wacharapluesadee, Supaporn; Buathong, Rome; Iamsirithawon, Sopon; Chaifoo, Walairat; Ponpinit, Teerada; Ruchisrisarod, Chanida; Sonpee, Chanikarn; Katasrila, Panticha; Yomrat, Siriporn; Ghai, Siriporn; Sirivichayakul, Sunee; Okada, Pilailuk; et al. (Frontiers in Public Health, 2020)
In resource-limited countries, early detection of novel pathogens is often challenging, due to financial and technical constraints. This study reports the efficacy of family-wide polymerase chain reaction (PCR) in screening, detecting and identifying the initial cases of the novel SARS-CoV-2 in Thailand. Respiratory secretions were collected from suspected individuals travelling from Wuhan, China to Thailand at the beginning of January 2020. Family-wide PCR assays yielded positive results for coronavirus in one traveller within 12 hours on January 8, 2020. Nucleotide sequences (290 bp) showed 100% similarity to SARS-CoV-2. The whole genome sequence was further characterized by Next Generation Sequencing (NGS) for confirmation. Family-wide PCR was used to detect several initial cases of COVID-19 in Thailand before customized specific primers and probe were available for real-time PCR testing. Combining family-wide PCR, as a rapid screening tool, with NGS, for full genome characterization, could facilitate early detection and confirmation of a novel pathogen and enable early containment of a disease outbreak.